Concordancing and writing: review of related literature - Kotamjani, Sedigheh Shakib; Hussin, Habsah; Tehrani, Hesam Tahsildar; Neissi, Sina (Faculty of Educational Studies, Universiti Putra Malaysia, 2017)
In recent years, ESL and some EFL teachers have emphasized student-centered learning and focused on Computer-Aided Language Learning (CALL) and the use of linguistic corpora through Data-Driven Learning (DDL). Corpus consultation has been integrated into second language writing classrooms for a few decades. Some studies have reported that corpus consultation is useful to some extent. The present study aimed to review the potential of concordancing in L2 writing using existing literature. Therefore, all these empirical studies provide useful information on the impact of corpus concordancing. The results of the review showed that learner would benefit from concordancing as a reference tool if they are trained adequately in corpus consultation. Moreover, it is implied that learner concordancing raised learners’ awareness in linguistics aspects and promote learner autonomy. Future studies are also suggested based on the gap identified in the reviewed studies.